The Individual Perception of Wage Inequality: A Measurement Framework and Some Empirical Evidence - Andreas Kuhn (Institute for the Study of Labor (IZA), 2015)
This paper presents a simple conceptual framework specifically tailored to measure individual perceptions of wage inequality. Using internationally comparable survey data, the empirical part of the paper documents that there is huge variation in inequality perceptions both across and within countries as well as survey-years. Focusing on the association between aggregate-level inequality measures and individuals' subjective perception of wage inequality, it turns out that there is both a high correlation between the two measures as well as a considerable amount of misperception of the prevailing level of inequality. The final part of the analysis shows that subjective inequality perceptions appear to be more important, in a statistical sense, in explaining variation in individual-level attitudes towards social inequality than objective measures of inequality. This underlines the conceptual and practical importance of distinguishing between subjective perceptions of inequality and the true level of inequality.
Keywords: D31; D63; J31; 330; inequality perceptions; inequality; attitudes towards social inequality; (mis-)perceptions of socio-economic phenomena